Spontaneous bodily coordination varies across affective and intellectual child-adult interactions - Cornejo, Carlos; Cuadros, Zamara; Carré, David; Hurtado, Esteban; Olivares, Himmbler (Frontiers in Psychology, 2024)
Research on child-adult interactions has identified that the morphology of bodily coordination seems to be sensitive to age and type of interaction. Mirror-like imitation emerges earlier in life and is more common during emotionally laden interactions, while anatomical imitation is acquired later and associated with cognitive tasks. However, it remains unclear whether these morphologies also vary with age and type of interaction during spontaneous coordination. Here we report a motion capture study comparing the spontaneous coordination patterns of thirty-five 3-year-old (20 girls; Mage = 3.15 years) and forty 6-year-old children (20 girls; Mage = 6.13 years) interacting with unacquainted adults during two storytelling sessions. The stories narrated the search of a character for an object (Predominantly Affective Condition) or her mother (Predominantly Intellectual Condition) inside a supermarket. Results show that children of both ages consistently coordinated their spontaneous movements towards adult storytellers, both in symmetric and asymmetric ways. However, symmetric coordination was more prominent in 3-year-old children and during predominantly emotional interactions, whereas asymmetric coordination prevailed in 6-year-old children and during predominantly intellectual interactions. These results add evidence from spontaneous interactions in favor of the hypothesis that symmetric coordination is associated with affective interactions and asymmetric coordination with intellectual ones.